Study of clinical and laboratory profile in alcoholic liver disease with emphasis on renal function - Hegde, Swati; Vishnar, Arun; Ramteke, Girish B. (International Journal of Research in Medical Sciences, 2017)
Background: Alcoholic liver disease is a major health care problem in India and accounts for increased economic burden. Chronic liver disease is most commonly complicated with renal dysfunction and this combination leads to significant morbidity and mortality. The aim was to study the clinical and laboratory profile and evaluation of renal function in alcoholic liver disease. Methods: Sixty consecutive patients presenting to a tertiary care hospital in central India with alcoholic liver disease were studied and their clinical and laboratory investigation noted and analysed. Results: The mean age at presentation was 45.18years. Fifty nine of them were male. Abdominal distension and jaundice were the most common presenting complaint. Fourteen (23%) patients presented with complications. Twenty six (43%) had severe anemia, 16 (27%) had thrombocytopenia and 23 (38.3%) had coagulopathy. The mean AST, ALT, bilirubin, ALP and albumin were 113.51 U/l, 62.16 U/l, 5.78 mg/dl, 211 U/l and 3.12 gm/dl respectively. On abdominal sonography fatty changes was seen in 20 (33%), Hepatomegaly in 20 (33%), Splenomegaly in 25 (41%) and PVD ≥13 mm in 11 (21%). The prevalence of renal dysfunction on the basis of reduced GFR was 30% which included all forms of renal failure in chronic liver disease. Serum creatinine level was increased in 20% of the patients. Blood urea was raised in 37%. Conclusion: The results of this study established most of the known facts about alcoholic liver disease in this part of the world. Not only liver function tests, patients with alcoholic liver disease have abnormal haematological and renal function too. Renal dysfunction was seen in significant number of patients.